Carbon dioxide levels in initial nests of the leaf-cutting ant Atta sexdens (Hymenoptera: Formicidae) - Sousa, Kátia K. A. [UNESP]; Camargo, Roberto S. [UNESP]; Caldato, Nadia [UNESP]; Farias, Adriano P. [UNESP]; Matos, Carlos A. O. [UNESP]; Zanuncio, José C.; Santos, Isabel C. L.; Forti, Luiz C. [UNESP] (Springer Nature, 2021)
Claustral foundation of nests by Atta sexdens Forel (Hymenoptera: Formicidae) involves great effort by its queens, solely responsible for the cultivation of the fungus and care for her offspring at this stage. The minimum workers, after 4 months, open access to the external environment to foraging plants to cultivate the symbiotic fungus, which decomposes the plant fragments and produces gongilidea nodules as food for the individuals in the colony. Colony gas exchange and decomposition of organic matter in underground ant nests generate carbon dioxide (CO2) emitted into the atmosphere. We described the carbon dioxide concentration in colonies in the field. The objective was to evaluate the carbon dioxide concentration in initial A. sexdens colonies, in the field, and their development. The CO2 level was also measured in 4-month-old colonies in the field, using an open respirometric system fitted with an atmospheric air inlet. The CO2 level of the respirometric container was read by introducing a tube into the nest inlet hole and the air sucked by a peristaltic pump into the CO2 meter box. The CO2 concentration in the initial colony was also measured after 4 months of age, when the offspring production (number of eggs, larvae, pupae and adult workers) stabilized. Ten perforations (15 cm deep) was carried out in the adjacent soil, without a nest of ants nearby, to determine the concentration of CO2. The composition of the nests in the field was evaluated after excavating them using a gardening shovel and they were stored in 250 ml pots with 1 cm of moistened plaster at the bottom. The CO2 concentration was higher in field nest than in adjacent soil. The concentration of carbon dioxide in A. sexdens nests in the field is higher than in those in the soil, due to the production of CO2 by the fungus garden and colony.